Pengetahuan Covid-19 Dengan PHBS Adaptasi Kebiasaan Baru Pada Masyarakat - Fitrianingsih, Rohma; Wahyudi, Dian Arif; Hardono, H; Putri, Riska Hediya (Universitas Aisyah Pringsewu (UAP) Lampung, 2021)
The COVID-19 pandemic was a rapid and sudden disaster that occurred in Indonesia in early 2020. This condition forced people to change their awareness of the importance of health protocols. Knowledge is one indicator of clean and healthy living behavior (PHBS) behaviour to prevent the chain of spreading the Covid-19 virus. The research was to determine the correlation between knowledge of Covid-19 with clean and healthy living behavior (PHBS) adaptation of new habits on the community at the Public Health Center of Sukarame in Sukarame Sub-District 2021. This type of research is quantitative research, with a descriptive correlational design using a cross-sectional approach. The sample used as many as 60 respondents who are visitors at the Public Health Center of Sukarame in Sukarame Sub-District. Taking the sample used incidental sampling technique. This research was carried out on three up to six February 2021. Bivariate analysis in this research used the Gamma Test. The results showed that the frequency distribution of knowledge of Covid-19 was high as many as 47 respondents (78.3%), and the frequency distribution of clean and healthy living behavior (PHBS) adaptation of new habits was 43 respondents (71.7%), which means the high category. Based on the results of the statistical test, a p-value of 0.001 (less than 0.05) was obtained which indicated that there was a correlation between knowledge of Covid-19 and clean and healthy living behavior (PHBS) adaptation of new habits on community at the Public Health Center of Sukarame in Sukarame Sub-District 2021. The conclusion in this research is that knowledge can improve clean and healthy living behavior (PHBS). It is expected that the results of this research will increase knowledge regarding the prevention of Covid-19 such as avoiding going to crowded places and public transportation, handling Covid-19 patients by self-isolation for 14 days, as well as the spread of covid-19 and increasing clean and healthy living behavior (PHBS) regarding hand washing for 20 seconds, consuming fruit. At least three times a day, do not touch the face when outside the house and it use gloves when cleaning household appliances.Abstrak: Pandemi covid-19 merupakan bencana cepat dan mendadak yang terjadi di Indonesia pada awal tahun 2020. Kondisi tersebut memaksa masyarakat merubah kesadaran pentingnya protokol kesehatan. Pengetahuan adalah salah satu indikator perilaku PHBS untuk mencegah rantai penyebaran virus covid-19. Tujuan penelitian ini adalah untuk mengetahui hubungan antara pengetahuan covid-19 dengan PHBS adaptasi kebiasaan baru pada masyarakat di Puskesmas Sukarame Kecamatan Sukarame Tahun 2021. Jenis penelitian ini adalah penelitian kuantitatif, dengan desain deskriptif korelasional menggunakan pendekatan cross sectional. Sampel yang digunakan sebanyak 60 responden yang merupakan pengunjung di Puskesmas Sukarame, pengambilan sampel menggunakan tekhnik insidental sampling. Penelitian ini telah dilaksanakan pada 3-6 Februari 2021. Analisis bivariat dalam penelitian ini menggunakan Uji Gamma. Hasil penelitian menunjukkan bahwa distribusi frekuensi pengetahuan covid-19 tinggi sebanyak 47 responden (78,3%), dan distribusi frekuensi PHBS adaptasi kebiasaan baru sebanyak 43 responden (71,7%) yang artinya kategori tinggi. Berdasarkan hasil uji statistik diperoleh p-value 0,001 (kurang dari 0,05) yang menunjukkan bahwa ada hubungan antara pengetahuan covid-19 dengan PHBS adaptasi kebiasaan baru pada masyarakat di Puskesmas Sukarame. Kesimpulan dalam penelitian ini adalah pengetahuan dapat meningkatkan PHBS. Diharapkan hasil penelitian ini menambah pengetahuan mengenai pecegahan covid-19 seperti menghindari pergi ketempat ramai dan transportasi umum, penanganan pasien covid-19 dengan melakukan isolasi mandiri selama 14 hari, serta penyebaran covid-19 dan meningkatkan PHBS mengenai cuci tangan selama 20 detik, mengkonsumsi buah minimal 3x sehari, tidak menyentuh wajah ketika berada diluar rumah serta menggunakan sarung tangan ketika membersihkan peralatan rumah.